Adolescents' Socio‐Motivational Relationships With Teachers, Amygdala Response to Teacher's Negative Facial Expressions, and Test Anxiety. (10th August 2015) - Raufelder, Diana; Hoferichter, Frances; Romund, Lydia; Golde, Sabrina; Lorenz, Robert C.; Beck, Anne
Abstract : The amygdala is essential for processing emotions, including the processing of aversive faces. The aim of this multimethodological study was to relate the amygdala reactivity of students ( N = 88) toward teachers' fearful and angry faces, to students' relationship with their teachers. Furthermore, students' neural responses during the perception of teachers' faces were tested as predictors of test anxiety (controlling for neuroticism as a potential trait anxiety effect). Multiple regression analysis revealed that students reporting high‐quality teacher–student relationships showed stronger amygdala activity toward fearful faces, which was related to worry. Furthermore, students with high levels of neuroticism tended to perceive their teachers as motivators and showed higher amygdala activity toward angry faces, which was related to the measures of emotionality.